2018
DOI: 10.1177/1932296818786486
|View full text |Cite
|
Sign up to set email alerts
|

Using Cluster Analysis to Understand Clinician Readiness to Promote Continuous Glucose Monitoring Adoption

Abstract: Some diabetes clinicians may benefit from tailored interventions and additional time and resources to empower them to help facilitate increased uptake of CGM technology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 32 publications
0
35
0
Order By: Relevance
“…Notably, there is increasing evidence suggesting that health care professionals’ attitude toward CGM constitutes a barrier to CGM use expansion. 45 In addition, Tanenbaum et al 46 have reported a readiness chart for clinicians (MDs and CDEs) who are likely to prescribe diabetes technology tools. Three “clinician personas” were described, based on their readiness to promote CGM technology and comfort in keeping up with technology advances.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, there is increasing evidence suggesting that health care professionals’ attitude toward CGM constitutes a barrier to CGM use expansion. 45 In addition, Tanenbaum et al 46 have reported a readiness chart for clinicians (MDs and CDEs) who are likely to prescribe diabetes technology tools. Three “clinician personas” were described, based on their readiness to promote CGM technology and comfort in keeping up with technology advances.…”
Section: Resultsmentioning
confidence: 99%
“…Educators were overall satisfied with the program as well and reported low difficulty with the different components overall. Device uploads were reported as the highest difficulty, which is an ongoing frustration in clinical practice as well 26,27 . Several months after the evaluation of this program, the device manufacturer released a cloudconnected app for Control-IQ, which will reduce burden with obtaining device downloads in the future.…”
Section: Discussionmentioning
confidence: 99%
“…The largest limitation is the time spent by diabetes educators and administrative staff. Time and workflow are ongoing concerns in our clinical practice, and are identified in the literature as a common barrier to clinicians' ability to embrace advanced diabetes technologies 18,26. It is not realistic that our Clinic could indefinitely support nurses spending 45 minutes of time following up on new HCL users when the task is not currently reimbursable by insurance.…”
mentioning
confidence: 99%
“…The use of cluster analyses in healthcare decision making is still relatively uncommon but appears to be gaining acceptance [17,18,19,20,21]. Our work builds upon a few previously published cluster analyses in diabetes, which focused on readiness of CGM and other diabetesrelated devices, self-management patterns in a pediatric population, and factors in uencing people with diabetes who have poorly controlled conditions [22,23,24,25,26]. These previous studies involved smaller numbers of participants from relatively homogeneous populations (e.g., T1DM registry) and/or more controlled conditions (e.g., clinical trial).…”
Section: Discussionmentioning
confidence: 99%